PREDICTORS FACTORS OF BLADDER INJURY IN PLACENTA ACCRETA SPECTRUM SURGERY AT A TERTIARY HOSPITAL - Akbar, Fariz Kemal; Daryanto, Besut; Satyagraha, Paksi (Indonesian Urological Association, 2026)
Objective: This study aims to determine the predictors factors associated to bladder injury sustained following placenta accreta spectrum surgeries. Material & Methods: This retrospective cohort study was conducted at the Saiful Anwar General Hospital from 2020-2024. Pregnant women with PAS undergoing hysterectomy or caesarean deliveries were included in the study population. Age, gestational age, number of previous cesarean deliveries, and placenta acreta index (PAI) Score were recorded. Univariate and multivariate analyses were performed to compare women with and without operative bladder injuries. Results: A total of 112 women were included in the study. The incidence of bladder injuries was 10,7%. Preoperative ultrasound examinations revealed an 84% concordance rate with surgical findings, confirming the diagnosis of placenta accreta spectrum. The average age of pregnant women with PAS was 33.71 ± 4.66 years, with the most common age range being 31-35 years (34.8%). In univariate analysis, gestational age, number of prior cesarean section, and PAI score include lacuna grade, myometrial thickness, and bridging vessel associated with risk of bladder injury. However, the number of prior cesarean sections and myometrial thickness measured by PAI showed a significant association in multivariate analysis. Conclusion: PAS condition carries a risk of bladder injury during surgery. Predictors factors associated to bladder injury of PAS cases include the number of prior cesarean section and myometrial thickness in PAI. Keywords: Bladder injury, placenta accreta spectrum, predictors factors.